Whole-genome sequencing of Tahe red deer (Cervus hanglu yarkandensis) reveals genetic diversity and selection signatures - Pi, Te; Yi, Wenfeng; Mao, Zengwei; Wang, Zhihua; Sun, Hao; Yan, Shouqing (Frontiers in Veterinary Science, 2025)
The Tahe red deer (TRD), domesticated and artificially raised from wild Tarim red deer, is valued for its high-quality antlers and ability to survive tough desert conditions. Nowadays, the decline in the population of TRD has significantly impacted their genetic diversity, posing a serious threat to their conservation and utilization. However, information based on whole-genome sequencing data of TRD is scarce, and the mechanisms underlying adaptive characteristics remain poorly understood. Additionally, research on Tahe red deer holds great importance for elucidating the evolutionary history and adaptability of the genus Cervus. This study aimed to investigate the genetic diversity, population structure, and selection signals of TRD using whole-genome sequencing data. The results revealed that TRD exhibited high inbreeding level and relatively low genetic diversity, and that TRD had a closer relationship with Cervus canadensis. Using three methods, including the fixation index, nucleotide diversity and cross-population extended haplotype homozygosity, there were 573 genes annotated in 2,303 overlapping candidate selection regions such as IL1R1, F13B, ARHGAP15, DCLK3, CACHD1, NDEL1, and UPF1, most of which were associated with adaptation to a hot arid environment. In summary, this study offered genomic markers and candidate genes associated with these traits, providing valuable insights for improving future breeding strategies of TRD.